DISTINCTIVE FEATURES OF PERIODONTAL STATUS IN EXPECTANT MOTHERS - Irina-Georgeta Sufaru; Maria-Alexandra Martu; Ioana Martu; George-Alexandru Maftei; Liliana Pasarin; Ionut Luchian; Silvia Martu; Sorina-Mihaela Solomon (Romanian Dental Association for Education, 2024)
Pregnancy is a unique physiological state characterized by hormonal fluctuations and immunological adaptations that can impact various aspects of maternal health, including oral health. The influence of pregnancy on periodontal status has been the subject of extensive research, with studies highlighting the association between gestation and changes in the oral cavity. Elevated levels of estrogen and progesterone during pregnancy have been implicated in the exacerbation of gingival inflammation and periodontal disease progression. Immunological changes, including alterations in immune cell function and cytokine production, further contribute to the heightened inflammatory response observed in the periodontium of pregnant individuals. While the precise mechanisms underlying the relationship between pregnancy and periodontal status continue to be elucidated, preventive measures such as oral hygiene education, regular dental check-ups, and timely periodontal treatment are crucial for promoting optimal oral health outcomes for both mother and child during gestation. Understanding the influence of pregnancy on periodontal status is essential for providing comprehensive prenatal care and ensuring the well-being of pregnant individuals and their offspring.